On Asking Questions During Geographic Field Trips: An Empirical Study on Pre-service Teacher Asking Questions by the Example of Northern Tuscany - Lindau, Anne-Kathrin; Renner, Tom (Journal of Geography Education, 2019)
Field trips belong to Geography‘s traditional methods. When on a field trip, participants can discover and analyze space from a multitude of perspectives. Thereby, asking questions plays a central role for inquiry–specifically when addressed to a given spatial entity. Participants asking questions engage actively and intensively with the field-trip‘s destination area. This paper aims at exploring the potential of asking questions for inquiry during field trips. In doing so, it focusses on how future Geography teachers formulate questions based on space and other basic concepts. Data collection happened with the help of a questionnaire containing both closed (Likert-scale) and open questions. The analysis relied on category-based qualitative content analysis. The results show that addressing questions to the destination area of a field trip is a useful way to explore teacher training students‘ use of basic concepts. While the students usebasic concepts in multiple ways, they focus solely on the concept of space as a container. Moreover, thecomplexity of the posed questions increases over time.
Keywords: teacher training, field trips, questions, inquiry, space and basic concepts